Nets – Knots – Lace: Early 16th century headdresses from East Tyrol - Nutz, Beatrix (Archaeological Textiles Review, 2019)
In an excavation carried out in 1968 four headdresses dating from the early to first half of the 16th century were discovered in a crypt in the parish church of Lienz in East Tyrol (Austria). All four headdresses are remarkably well preserved and two of them reveal techniques that are surprising considering the early date. A hairnet with macramé knots and a coif adorned with bobbin lace most likely date before 1509 making them the earliest extant examples of macramé and bobbin lace to date. This paper gives an account of the finds and considers the implications these headdresses might have on the history of lace.